Analysis of Sea Surface Dynamics during the Coastal Floods in Manado - Audia Azizah Azani; Usman Efendi (Geosfera Indonesia, 2023)
Coastal flooding is one of the serious problems facing most coastal areas in the world. On January 17 and December 7, 2021, coastal flooding hit the coastal area of Manado, North Sulawesi, Indonesia. The disaster disrupted economic activities on the coast of Manado Bay. This study analyzed the dynamics of the atmosphere and the sea during coastal flood events using water level data from the Geospatial Information Agency, which was then filtered to separate residual and atmospheric tide, and oceanographic reanalysis data of Wavewatch-III from BMKG Ocean Forecast System (OFS). The results show that events on January 17 and December 7, 2021, coincided with the occurrence of the maximum tide. The residual water level shows a significant value of around 0.2 – 0.3 m, indicating the influence of atmospheric phenomena on sea level rise. According to oceanographical data, the local wind is the main factor of flood occurrence, which is shown by wind speed data which increased wave height significantly to 1,5 m on January 17, 2021, and to 2,0 m on December 7, 2021, around Manado Bay coast. Another factor that might contribute to the event is Manado's land morphology. Further study must be conducted to discover the influence of land morphology on coastal floods.